Earthworms and Plant Residues Modify Nematodes in Tropical Cropping Soils (Madagascar): A Mesocosm Experiment - Cécile Villenave; Bodo Rabary; Emilie Kichenin; Djibril Djigal; Eric Blanchart (Applied and Environmental Soil Science)
Free-living nematodes present several characteristics that have led to their use as bioindicators of soil quality. Analyzing the structure of nematofauna is a pertinent way to understand soil biological processes. Earthworms play an important role in soil biological functioning and organic matter dynamics. Their effects on soil nematofauna have seldom been studied. We studied the effect of the tropical endogeic earthworm, Pontoscolex corethrurus, on nematode community structure in a 5-month field mesocosm experiment conducted in Madagascar. Ten different treatments with or without earthworms and with or without organic residues (rice, soybean) were compared. Organic residues were applied on the soil surface or mixed with the soil. The abundance of nematodes (bacterial and fungal feeders) was higher in presence of P. corethrurus than in their absence. The type of plant residues as well as their localisation had significant effects on the abundance and composition of soil nematodes. The analysis of nematode community structure showed that earthworm activity led to an overall activation of the microbial compartment without specific stimulation of the bacterial or fungal compartment.